Antigen-specific inhibition of high avidity CTL target lysis by low avidity CTL via trogocytosis: a novel mechanism of immune regulation - Chung, Brile (2014)
Current vaccine conditions predominantly elicit low avidity cytotoxic T-lymphocytes (CTLs), which are non-tumor-cytolytic but indistinguishable by tetramer staining or Enzyme-Linked ImmunoSpot from high avidity CTLs. Using CTL clones of high or low avidity for melanoma antigens, we show that low avidity CTLs can inhibit tumor lysis by high avidity CTLs in an antigen-specific manner. This phenomenon operates in vivo: high avidity CTLs control tumor growth in animals, but not in combination with low avidity CTLs specific for the same antigen. The mechanism involves stripping of specific peptide-major histocompatibility complexes (pMHC) via trogocytosis by low avidity melanoma-specific CTLs without degranulation, leading to insufficient levels of specific pMHC on target cell surface to trigger lysis by high avidity CTLs. As such, peptide repertoire on the cell surface is dynamic and continually shaped by interactions with T cells. These results describe immune regulation by low avidity T cells and have implications for vaccine design.